Different Perceptions among Women and Their Physicians Regarding Contraceptive Counseling: Results from the TANCO Survey in Brazil - Rogério Bonassi Machado; Thaís Emy Ushikusa; Ilza Maria Urbano Monteiro; Cristina Aparecida Falbo Guazzelli; Zsuzsanna Jarmy di Bella; Carlos Alberto Politano; Luís Carlos Sakamoto (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective The optimal use of contraceptive methods requires that women participate in targeted choice of methods that meet their individual needs and expectations. The Thinking About Needs in Contraception (TANCO) study is a quantitative online survey of the views of health professionals and women on aspects of contraceptive counseling and contraceptive use. Methods Physicians and women attending clinics for contraception were invited to complete online questionnaires. The research explored the knowledge and use of contraceptive methods, satisfaction with the current method and interest in receiving more information on all methods. Aspects related to contraceptive practice among physicians were gathered in parallel. The results obtained in the Brazilian research were compared with those of the European research, which involved 11 countries. Results There was a high prevalence of contraceptive use and general satisfaction with the current method. A total of 63% of the women were using short-acting contraceptive (SAC) methods, and 9% were using a long-acting reversible contraceptive (LARC). Sixty-six percent of women were interested in receiving more information on all methods; 69% of women said they would consider LARC if they received more comprehensive information about it. Health professionals tend to underestimate the interest of women in receiving information about contraception in general, and more speciﬁcally about LARCs. Conclusion Despite the high levels of use and satisfaction with the current methods, women were interested in receiving more information on all contraceptive methods. Structured contraceptive counseling based on individual needs and expectations may lead to greater knowledge and a greater likelihood of proper contraceptive choice.